Phylogeography and ecological niche modeling suggest southward expansion of Morinda officinalis How in China - Zhang, Chaoyu; Zhang, Miao; Huang, Xuehui; Lan, Qingtong; Zhu, Hua; Huang, Yong; Tian, Hui (Frontiers in Plant Science, 2025)
Morinda officinalis How is a traditional medicine plant that is currently native to the tropical and subtropical mainland as well as the islands of China. The effects of geological movements and Quaternary climate fluctuations on M. officinalis may be analyzed by genealogical geography in conjunction with ecological niche simulation. We performed Bayesian phylogenetic analysis of M. officinalis using chloroplast (rbcL, matK, and trnH-psbA) and nuclear gene sequence (ITS2) genealogy and simulation of the distribution of M. officinalis in the Chinese region. Low nucleotide and haplotype diversity, and genetic geographic structure of M. officinalis indicated the separation of the species into two lineages at 35.91 Mya. The optimal habitat of M. officinalis varied greatly during the Last Interglacial, Last Holocene, and Middle Holocene periods as well as in the current period. The species experienced expansion during the Last Interglacial and contraction during the Last Holocene. A large-scale migration occurred from the Tibetan Plateau to southeastern China, and the Shiwan and Liuwan Mountains in southern Guangxi, as well as the Dinghu Mountains in Zhaoqing, Guangdong, and the Ehuangzhang Mountains in Yangjiang, Guangdong, which were the principal Quaternary ice age refuges for M. officinalis. The island lineages of M. officinalis diverged before the emergence of the Qiongzhou Strait. The historical ancestral origin of M. officinalis is thought to be the Tibetan Plateau and the southward migration in the early Miocene and subsequent in situ diversification may explain the diversity of M. officinalis. Our results provide phylogenetic evidence for the origin of M. officinalis, reveal the process of diversification, and indicate that the species adapted to a timeline of major geological and climatic episodes rather than localized, episodic, and rate-varying events.